P107 MULTIMODALITY IMAGING IN ASCENDING AORTA PSEUDO–ANEURYSM COMPLICATED BY MOBILE TROMBUS SYMPTOMATIC FOR RECURRENT ISCHEMIC STROKE. (18th May 2022) - Monari, D; Mei, D; Mantovani, F; Guiducci, V; Navazio, A
Abstract:  : A 80–year–old male patient was admitted to hospital with a clinical picture of Broca's aphasia. The patient had arterial hypertension, diabetes, chronic kidney disease and peripheral vasculopathy. In remote cardiological history he presents long standing persistent atrial fibrillation on OAC and he had a biological aortic valve prosthesis (Medtronic 23). Overall time in the therapeutic range (INR 2.0–2.5) was adequate considering the presence of atrial fibrillation. A CT scan was performed on suspicion of stroke, showing a recent ischemic lesion in the left middle temporal region complicated by same–site subarachnoid blood suffusion. During the hospital stay there was a recurrence of the aforementioned symptoms: at the CT check a new acute ischemic same–site lesion and a new ischaemic lesion at the left temporal site was highlighted. In the suspicion of a cardio–embolic origin of cerebro–vascular events, it was decided to carry out imaging for the study of the aorta and heart cavities to exclude embolic sources. Given the patient's comorbidities and the reported allergies (contrast medium with angioedema–like reaction at a previous CT) it was decided to perform transesophageal echocardiography (TEE) first. TEE documented the presence of a saccular aneurysm of probable pseudo–aneurysmatic nature, which extends from 20 mm from the valvular plane, characterized by pedunculated, mobile thrombotic apposition, adhered to the internal collar, projecting into the psueudo–aneurysmatic cavity (image 1). This finding was confirmed and better characterized with the help of the real time three–dimensional echocardiographic method (image 2). To confirm and better characterize the extension of the pseudo–aneurysm and plan any strategy, a CT scan with contrast medium was required. Performing contrast–enhanced CT, after careful preparation with premedication with antihistamine and cortisone, confirmed the finding of pseudo–aneurysm of the ascending aorta, but the pedunculated thrombotic apposition was less clearly evidenced compared with TEE (giving the superior temporal resolution of TEE) (image 3). The case was therefore assessed in Heart Team and the patient was scheduled for surgically exclusion of the pseudo–aneurysm. Conclusion: In our case a multimodality imaging approach was used to diagnose and confirm the presence of ascending aorta pseudo–aneurysm complicated by pedunculated thrombotic apposition inside it, symptomatic for recurrent ischaemic stroke.